2018
DOI: 10.5606/fng.btd.2018.010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of vitamin B12, folate, and ferritin levels of inpatients in a psychiatry clinic: A one-year retrospective study

Abstract: Objectives:This study aims to compare the vitamin B12, folate, and ferritin levels of inpatients in a psychiatry clinic. Materials and methods:The study included 286 inpatients (178 males, 108 females; mean age 35.4±12.9 years; range, 15 to 76 years) treated in Adiyaman University Training and Research Hospital psychiatry clinic between 01 January 2017 and 31 December 2017. Patients' diagnoses and vitamin B12, folate, and ferritin levels were examined retrospectively. Results:The most common diagnoses were sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…In a study involving all psychiatric patients treated at the hospital, a non-significant lower ferritin level was found in the group with OCD compared to other psychiatric diseases such as depression, bipolar, and schizophrenia. [43] In another study conducted in children with Tourette's syndrome, which is known to be associated with OCD, ferritin levels were found to be low. In this study, it was reported that patients' tics decreased with iron supplementation.…”
Section: Discussionmentioning
confidence: 96%
“…In a study involving all psychiatric patients treated at the hospital, a non-significant lower ferritin level was found in the group with OCD compared to other psychiatric diseases such as depression, bipolar, and schizophrenia. [43] In another study conducted in children with Tourette's syndrome, which is known to be associated with OCD, ferritin levels were found to be low. In this study, it was reported that patients' tics decreased with iron supplementation.…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9][10][11] Küçük şehirlerde erişkin psikiyatrisi servisleri çocuk ve ergen psikiyatrisi servislerinin yerini doldurmaya çalışmaktadır. 12 Erişkin psikiyatri servislerinde yatan çocuk yaş grubundaki hastaların değerlendirildiği çalışmalar kısıtlı sayıdadır. 13,14 Halbuki bizim hipotezimiz çocuk ve ergen psikiyatri servisleriyle karşılaştırıldığında, erişkin psikiyatrisi servislerinde yatan çocuk ve ergen hastaların tanı ve yaş başta olmak üzere sosyodemografik değişkenler ve hastalık özellikleri açısından değişkenlik göstereceği yönündedir.…”
Section: Introductionunclassified